2012
DOI: 10.1088/2041-8205/745/2/l32
|View full text |Cite
|
Sign up to set email alerts
|

The Period Change of the Cepheid Polaris Suggests Enhanced Mass Loss

Abstract: Polaris is one of the most observed stars in the night sky, with recorded observations spanning more than 200 years. From these observations, one can study the real-time evolution of Polaris via the secular rate of change of the pulsation period. However, the measurements of the rate of period change do not agree with predictions from state-of-the-art stellar evolution models. We show that this may imply that Polaris is currently losing mass at a rate ofṀ ≈ 10 −6 M ⊙ yr −1 based on the difference between model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 26 publications
5
43
0
1
Order By: Relevance
“…These changes are not secular, i.e., not a function of evolution, but this cause is unclear. A similar period drift has been suspected for the classical Cepheid Polaris (Turner et al 2005;Neilson et al 2012a). If this period drift is occurring in β Cephei variable stars then it could explain why there are such high rates of period change for only three stars.…”
Section: Discussionsupporting
confidence: 64%
“…These changes are not secular, i.e., not a function of evolution, but this cause is unclear. A similar period drift has been suspected for the classical Cepheid Polaris (Turner et al 2005;Neilson et al 2012a). If this period drift is occurring in β Cephei variable stars then it could explain why there are such high rates of period change for only three stars.…”
Section: Discussionsupporting
confidence: 64%
“…In terms of the Pp relation, these differences will not lead to a systematic shift of the Pp relation but will lead to a greater scatter of the p-factors used to fit a relation. Recent observations show that Cepheids undergo mass loss (Marengo et al 2010a,b;Barmby et al 2011;Matthews et al 2011;Neilson et al 2012). This mass loss is believed to lead to a far-infrared excess and may be consistent with the K-band excess observed by Kervella et al (2006);Mérand et al (2006Mérand et al ( , 2007.…”
Section: Why Do Theory and Observations Disagree?mentioning
confidence: 77%
“…Therefore, it can be concluded that Polaris must be more distant and is consistent with the previously measured Hipparcos parallax. Similarly, the pulsation mode for Polaris has been previously derived based on the measured distance, hence radius, and combined with a period-radius relation (Neilson et al 2012a;Turner et al 2013). At a distance of 118 pc, the predicted mean radius is R = 41.1 R .…”
Section: Constraining the Distancementioning
confidence: 92%
“…Hence, Polaris is evolving along the third crossing of the instability strip on the Cepheid blue loop and its observed CNO abundances are consistent with dredge up during the previous red giant stage. Neilson et al (2012a) further suggested that to account for discrepancy between measured and predicted rates of period change, Polaris must be losing mass in an enhanced stellar wind withṀ = 10 −7 −10 −6 M yr −1 . Our understanding of Polaris is biased by the assumed distance, therefore measuring a precise and consistent distance is crucial.…”
Section: Introductionmentioning
confidence: 99%